(untitled) (Indonesian Journal of Science and Technology, 2025)
Wind energy is vital for transitioning to renewable sources, reducing reliance on fossil fuels, and mitigating climate change. Harnessing wind power provides sustainable solutions to meet global energy demands. The systematic review provides valuable insights into recent advancements in blade design for wind turbines, crucial for optimizing efficiency, and sustainability in wind energy systems. The study emphasized advancements in Horizontal Axis Wind Turbines, concentrating on efficiency enhancements with numerical simulations and optimization strategies. Additionally, it explored developments in Vertical Axis Wind Turbine technology, notably hybrid rotor systems, and primarily utilized wind turbine airfoils over the past 25 years. Many researchers focused on optimizing aerodynamic systems using advanced numerical simulations, experiments, and optimization techniques, stressing the significance of achieving optimal lift-to-drag ratios. Furthermore, factors like bend-twist coupling and stall characteristics to prolong turbine lifespan and maximize power extraction were investigated. The interdisciplinary nature of wind energy research emphasizes collaborative efforts to address challenges and foster innovation, driving progress toward sustainable development goals. This review also supports current issues in the sustainable development goals (SDGs).